Beam dynamics issues in undulator based PPA - Moiseev, V.A.; Paramonov, V.V.; Flöttmann, K. (Вопросы атомной науки и техники, 2006)
The analysis of the beam dynamics simulation for an undulator based Positron Pre-Accelerator was carried out to produce a high positron capture with the reliable and reasonable design solution. From beam dynamics and taking into account a lot of parameters for optimization the attempt to ground the proposal PPA design was done. The possible choice of any other design solution is discussed.